Dynamic of organic matter and microbial biomass in a soil under different management systems in the Western Amazon - Moreira, Adônis; Malavolta, Eurípedes (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the alterations of the microbial biomass activity as an indicator of C and N dynamics in a soil submitted to the succession of plant cover and management in the Western Amazon. The work was carried out in two chronosequences: CA – a succession from primary forest to a three years old cupuaçu (Theobroma grandiflorum) plot – and CB – a succession from primary forest to an eight years old Brachiaria humidicola pasture and a three years old cupuaçu plot. The succession primary forest-pasture-cupuaçu affects negatively the stock of the soil carbon, with significant decrease of organic matter and C of the soil microbial biomass. The primary forest presents lower metabolic quotient and higher C/N ratio of the biomass, which results in less carbon loss. The N of the microbial biomass found in the 0–10 cm layerir respective of the management adopted, increases significantly in the cupuaçu plot and the total N decreases. Ammonium concentration decreases according to soil depth, but this does not occur with nitrate.